2016 SIIL Annual Meeting - Sustainable intensification through better integration of crop and livestock production systems in Burkina Faso - Wijk, Mark T. van (Kansas State University, 2016)
Dr. Mark van Wijk, Co-PI of the Burkina Faso subaward funded by the Feed the Future Innovation Lab for Collaborative Research on Sustainable Intensification (SIIL), presents his project to the SIIL community.